Implementation of Adaptive Modal Pushover Analyses (VMPA-A) to 20-Storey Los Angeles SAC Steel Building Subjected to Bi-directional Ground Motions - Sürmeli, Melih; Yüksel, Ercan; OSMAK, ÖZGE (Springer Science and Business Media Deutschland GmbH, 2024)
In this study, an adaptive modal pushover analysis procedure (VMPA-A) is implemented in the 20-story Los Angeles SAC Steel building. The method considers the changes in the dynamic characteristics and bi-directional ground motion effects simultaneously with the help of the hybrid-spectrum concept. Two different approaches are used to calculate displacement demands for each mode. The first one is equal displacement rule and the second is performing nonlinear time history analyses (NTHA) to modal single degree of freedom systems (SDOF). VMPA-A procedure is implemented by using a MATLAB-based computer program, DOC3D. The building is modeled with both SAP2000 and DOC3D programs. Cross-checks are done between two programs by performing eigenvalue and pushover analyses. As an accepted “exact solution”, NTHAs are used to check the accuracy of the VMPA-A procedure. Fourteen ground motion records, which were selected from the PEER NGA-West2 Database, are used in NTHAs by using SAP2000. The response parameters of storey shears, storey displacements, storey drifts, and column and beam curvatures are discussed by comparing the results of VMPA-A with nonlinear time history analyses. Good estimates are observed for storey displacements, storey shears, and storey drifts. Although the second approach in the calculation of displacement demands gives closer results to NTHA, the obtained demand parameters from the equal displacement rule are conservative. Storey drift and beam curvature distributions seem to be in a similar trend. Larger values for lower stories and smaller values for the upper stories are obtained with respect to the average of NTHAs. However, beam curvature distribution can not be predicted by VMPA-A, especially for the upper stories of the building. The column curvature results are in good agreement with NTHA results. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.
7th International Conference on Earthquake Engineering and Seismology, 7ICEES 2023
Keywords: Adaptive Pushover; Bi-directional Ground Motion; Hybrid Spectrum; Modal Pushover; Nonlinear Analysis; VMPA; VMPA-A